The Role of Organizational Commitment in Mediating the Effects of Work-Family Conflict and Job Satisfaction on Employee Turnover Intention at Ibah Luxury Villa in Ubud - PUSPITAWATI, Anak Agung Tirta; MARTADIANI, A.A.Media; DHARMANEGARA, Ida Bagus (PT Keberlanjutan Strategis Indonesia, 2025)
The growth of Bali's tourism sector, especially in hospitality, has increased demand for skilled workers. However, high turnover intention is a challenge, as seen at Ibah Luxury Villa, where turnover exceeds the 10% annual threshold. Contributing factors include work-family conflict, limited promotion opportunities, and low organizational commitment. This study aims to examine the role of organizational commitment in mediating the influence of work-family conflict and job satisfaction on employee turnover intention at Ibah Luxury Villa in Ubud. The population in this study was all 62 employees at Ibah Luxury Villa in Ubud. Since the population size was only 62, all members of the population were used as respondents; in other words, this was a census study. The data collection method was a questionnaire. The analysis technique used to answer the hypotheses was inferential analysis using Partial Least Squares (PLS). The study found that work-family conflict had a significant positive effect on turnover intention, while job satisfaction did not. Both work-family conflict and job satisfaction significantly influenced organizational commitment, but organizational commitment did not affect turnover intention nor mediate the relationships. This indicates that work-family conflict directly drives turnover intention, while job satisfaction and commitment are not strong predictors. Companies should address work-family conflict through work-life balance initiatives and strengthen commitment with appreciation and empathetic communication. Retention strategies must be comprehensive, beyond just satisfaction or commitment.